β-sitosterol inhibits trimethylamine production by regulating the gut microbiota and attenuates atherosclerosis in ApoE–/– mice - Wu, Weiping; Liu, Wugao; Wang, Huafu; Wang, Wei; Chu, Weihua; Jin, Jing (Frontiers in Cardiovascular Medicine, 2022)
The intestinal microbial metabolite trimethylamine (TMA), which is activated by flavin monooxygenase (FMO) to produce trimethylamine-N-oxide (TMAO), has been implicated in the pathogenesis of atherosclerosis, leading to the development of therapeutic strategies for atherosclerosis. This study aimed to investigate whether β-sitosterol can inhibit TMA production in ApoE−/− mice by reshaping the gut microbial structure. 16S rDNA sequencing of the gut microbiota showed that β-sitosterol has beneficial effects on intestinal flora function, especially the inhibition of bacteria genera that contain the gene cholintrimethylamine lyase, which is responsible for the major pathway for TMA production. In parallel, β-sitosterol effectively reduced the TMA, FMO3 and TMAO levels while ameliorating the atherosclerotic plaques of AS mice. Moreover, β-sitosterol could alleviate cholesterol metabolism and the inflammatory response, and improve the antioxidant defense capacity. These studies offer new insights into the mechanisms responsible for the antiatherosclerotic effects of β-sitosterol, which targets the microbiota-metabolism-immunity axis as a possible therapy for atherosclerosis.